2006
DOI: 10.1016/j.jmoneco.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border trading as a mechanism for implicit capital flight: ADRs and the Argentine crisis

Abstract: Cross-listed shares may confound government efforts to control capital outflows by providing a legal means through which investors can transfer their wealth outside the country. We study the recent experience of investors in Argentina and Venezuela who while subject to capital controls, were able to purchase cross-listed shares using local currency, convert the shares into dollardenominated shares, re-sell them in New York and deposit the dollar proceeds in U.S. bank accounts. We show that capital controls dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…These financial controls were intended to ward off a devaluation of the peso, effectively providing incentives for Argentineans to invest in their domestic stock market. According to Auguste et al (2006), (page 2) ''in contrast to the experiences of other emerging markets, the crisis appears to have 'good news' for the Argentinean stock market". They also find that local market factors became more important in pricing CL stocks in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…These financial controls were intended to ward off a devaluation of the peso, effectively providing incentives for Argentineans to invest in their domestic stock market. According to Auguste et al (2006), (page 2) ''in contrast to the experiences of other emerging markets, the crisis appears to have 'good news' for the Argentinean stock market". They also find that local market factors became more important in pricing CL stocks in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Several interesting studies consider the capital control episode in Argentina 2001/02 and find that prior to the devaluation of the peso, ADRs were traded at a price discount relative to their corresponding underlying stocks (e.g. Melvin (2003); Kadiyala (2004); Levy Yeyati et al (2004); Auguste et al (2006); Eichler et al (2009)). Melvin (2003), Levy Yeyati et al (2004) and Auguste et al (2006) attribute this finding to the fact that Argentinians were willing to pay a premium on domestic stocks in order to convert them into ADRs and then cash them into U.S. dollars -a legal way to circumvent the capital controls.…”
Section: Introductionmentioning
confidence: 99%
“…Melvin (2003); Kadiyala (2004); Levy Yeyati et al (2004); Auguste et al (2006); Eichler et al (2009)). Melvin (2003), Levy Yeyati et al (2004) and Auguste et al (2006) attribute this finding to the fact that Argentinians were willing to pay a premium on domestic stocks in order to convert them into ADRs and then cash them into U.S. dollars -a legal way to circumvent the capital controls. Kadiyala (2004) and Eichler et al (2009), on the other hand, argue that this relative discount reflects the market expectations of the true exchange rate that would result after the breakdown of the peg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no restriction on the conversion of Argentinean stock to ADRs(Auguste et al, 2006), and such conversions have been shown to aid capital flight during Argentinean crisis. This is the same case in Egypt, as supported by data obtained from the Egyptian Depository and Clearing House.…”
mentioning
confidence: 99%